Land suitability analysis for sandalwood plantation in Timor island - Sumardi; M. Hidayatullah; Dhany Yuniati; Bayu Adrian victorino (Jurnal Penelitian Kehutanan Wallacea, 2016)
Sandalwood population in Timor Island has been on a decrease at an alarming rate. The decrease reached 85% in 10 years, from 1987-1988 and 1997-1998. The present status of sandalwood on the Timor Island has been included as a vulnerable specie. Sandalwood cultivation and recovery efforts is systematic, this involves a planned process. To achieve any significant success, it must be supported by data and information about the location suitable for the growth of sandalwood. This study aims to provide data and information on the land suitability for sandalwood (Santalum album Linn.) in Timor Island. The study was conducted by analysis of soil chemistry and physics and biophysical conditions overlay with FAO procedure (1976). The analysis showed an actual suitability area for development of sandalwood in each district are as follows: Belu of 125,216.69 ha (51.32%), Timor Tengah Utara of 163,554.16 ha (61.26%), Timor Tengah Selatan of 278,818.77 ha (70.64%), Kupang of 263,677.77 ha (44.73%), Kupang City of 8994.48 ha (49.89%) of the total land area of each district.